Математичне моделювання внутрiшньої структури 3D тiла на основi трьох рентгенiвських знiмкiв у трьох взаємоперпендикулярних ракурсах - Сергiєнко, I.В.; Литвин, О.О. (Видавничий дім "Академперіодика" НАН України, 2008)
The explicit description of a class of functions of three variables that are a mathematical model of the inner structure of a 3D body (density, attenuation constant), which can be restored by three X-ray pictures in mutually perpendicular aspects is given.